Low-Power Optically Controlled Patch Antenna of Reconfigurable Beams - Deshuang Zhao; Yifei Han; Feng Liang; Qiaoli Zhang; Bing-Zhong Wang (International Journal of Antennas and Propagation)
A novel compact beam-reconfigurable patch antenna based on light control of no more than 30 mW optical powers is successfully demonstrated. It consists of one T-shape driven patch and one slot-etched parasitic patch. A silicon dice is employed as the photoconductive switch that is bridged across the slot center for optical control of reconfigurable beams. The antenna greatly reduces the total optical powers required for reconfigurable beams. Such design is based on the fact that the current phase change of the parasitic patch is sensitive to the conductivity of the silicon dice. A few conductivity changes of the silicon dice induced by the optical light can lead to a big phase change of the parasitic patch currents, eventually resulting in reconfigurable beams with low optical power requirement.